2015
DOI: 10.12659/msm.892112
|View full text |Cite
|
Sign up to set email alerts
|

Superselective Renal Artery Embolization in the Treatment of Iatrogenic Bleeding into the Urinary Tract

Abstract: BackgroundThe aim of this study was to evaluate the efficacy of superselective renal artery embolization in patients with bleeding into the urinary system.Material/MethodsFrom 2007 to 2012, 20 patients were treated with superselective renal artery embolization for bleeding after percutaneous nephrolithotomy (PCNL), nephron-sparing surgery (NSS), including 1 patient with AVF after PCNL. During the procedure, embolization material was injected through a microcatheter to stop the bleeding. Embolization materials … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 8 publications
1
19
0
Order By: Relevance
“…As materials have evolved and experience has been accrued with endovascular procedures, indications have come to include a vast spectrum of conditions including angiomyolipomas, vascular malformations, preoperative embolizations with the objective of attenuating intraoperative bleeding, 2,6 bleeding caused by iatrogenic injuries (percutaneous nephrolithotomy, biopsy, nephrostomy), ruptures of renal masses and penetrating and blunt renal traumas. 7,8 The availability of low profile catheters and more precise embolic agents have dramatically reduced morbidity associated with the procedure. 6 The majority of RAMLs are diagnosed incidentally, 2,3 because 60% are asymptomatic; and while the tumoral growth rate is unpredictable, the tendency is that growth will occur.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…As materials have evolved and experience has been accrued with endovascular procedures, indications have come to include a vast spectrum of conditions including angiomyolipomas, vascular malformations, preoperative embolizations with the objective of attenuating intraoperative bleeding, 2,6 bleeding caused by iatrogenic injuries (percutaneous nephrolithotomy, biopsy, nephrostomy), ruptures of renal masses and penetrating and blunt renal traumas. 7,8 The availability of low profile catheters and more precise embolic agents have dramatically reduced morbidity associated with the procedure. 6 The majority of RAMLs are diagnosed incidentally, 2,3 because 60% are asymptomatic; and while the tumoral growth rate is unpredictable, the tendency is that growth will occur.…”
Section: Discussionmentioning
confidence: 99%
“…2 Criteria for intervention include diameter greater than 4 cm (some authors state 3.5 cm), intratumoral aneurysms larger than 4-5 mm 1,2 and pain, active hemorrhage, 1 multiple RAMLs, bilateral RAMLs or unilateral RAML when the patient only has one kidney, and patients with tuberous sclerosis complex. 1,2,7 Several different studies have demonstrated the efficacy of embolization for treatment and prevention of hemorrhage. [1][2][3][4] The procedure can be performed under local anesthesia, with or without sedation, but some authors believe that the procedure can be conducted more quickly and with greater safety under general anesthesia.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations